When More Information Means Less Consumer Acceptance of Innovative Food Technologies - Levke Walten; Klaus-Peter Wiedmann; Steffen Schmidt (Marketing Review St.Gallen, 2021)
Many technological food innovations that offer desirable added value tend to be rejected by consumers. This study investigates explicit and implicit consumer acceptance and the role that information about innovative food products plays in consumer decision making. The results show that both explicit and implicit processes influence consumer acceptance.
Keywords: 650